HAMBATAN SISTEM GURU KELAS DALAM MENINGKATKAN KOMPETENSI MENGAJAR DI SEKOLAH DASAR - Itsnain Al-Fajrin; La Sisi; Sasmin Sasmin (Universitas Sulawesi Tenggara, 2020)
Abstract: Barriers to the Class Teacher System in Improving Teaching Competence in Elementary Schools. The purpose of this study was to explore and find out the barriers to the classroom teacher system in improving the teaching competence of teachers at Public Elementary School Tinete I. This type of research is descriptive qualitative. The subjects of this research are 6 teachers and 1 principal at Public Elementary School Tinete I. Research instrument is in the form of interviews and documentation. Qualitative description data analysis techniques. Based on the results of research on the barriers to the classroom teacher system in improving teacher teaching competence at Public Elementary School Tinete I that there is a discrepancy between the professional competence of the teacher and several subject areas and fields of study being taught.Keyword : Resistance, Teacher, Class, Competence, Teach